The Influence of Batang Napier Media on the Learning Outcomes of Class III Elementary School Students - Qiftiyah, Maratul; Yunianto, Teguh; Hidayati, Atika Nur; Sari, Tri Maya (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
This research aims to determine whether or not there is an influence of Napier learning media on the mathematics learning outcomes of class III MI NU Sumber Agung students. This type of research is a type of experiment (quasi-experiment). The population in this study were classes III A, III B, and III C MI NU Sumber Agung. The sample in this study was selected by drawing lots and class III A was selected as the experimental class and class III B as the control class. Based on data analysis and hypothesis testing using the t test, t is obtainedcount amounted to 2,554 and ttable of 2.010 at the significance level α = 5%, then tcount> ttable, as a result H0rejected, so it can be concluded that there is a difference in the learning outcomes of students taught using Batang Napier media with students taught using the repeated multiplication method. So, with these differences, it can be said that there is an influence of the use of Napier stem media on the learning outcomes of students in class III MI NU Sumber Agung